2018
DOI: 10.15252/embr.201845824
|View full text |Cite
|
Sign up to set email alerts
|

Trimming it short: PNLDC1 is required for piRNA maturation during mouse spermatogenesis

Abstract: Transposon silencing within the germ line requires the proper processing of piRNA intermediates. However, the enzyme that is required for piRNA 3′ end maturation in vertebrates remained enigmatic. Nishimura et al in this issue of EMBO Reports and two independent studies now identified PNLDC1 as the exonuclease that is responsible for piRNA 3′ end processing and transposon silencing during mouse spermatogenesis. Together, these studies establish PNLDC1 as the piRNA 3′ end trimmer in mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…The extent to which the regulation of PCD might still be relevant to eTudor and piRNA function, despite the loss of the DCD domain, remains to be elucidated, but there is evidence suggesting that it could be considerable. In the light of the putative evolutionary connection between the ancient form of PCD and the evolution of the eTudors and the piRNA network, it seems more explicable that conserved piRNA biogenesis factors Tudor-KH and MitoPLD/Zucchini are mitochondrially localized, perinuclear piRNA processing germ granules are also closely associated with mitochondria in addition to nuclear pores, and that reported phenotypes of many piRNA factor mutants include induction of PCD and/or germline mortality [ 75 , 140 144 ]. PCD is an important part of tissue differentiation, and piRNAs can prevent ectopic expression of somatic genes that might contribute to PCD or senescence of the germline [ 145 , 146 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which the regulation of PCD might still be relevant to eTudor and piRNA function, despite the loss of the DCD domain, remains to be elucidated, but there is evidence suggesting that it could be considerable. In the light of the putative evolutionary connection between the ancient form of PCD and the evolution of the eTudors and the piRNA network, it seems more explicable that conserved piRNA biogenesis factors Tudor-KH and MitoPLD/Zucchini are mitochondrially localized, perinuclear piRNA processing germ granules are also closely associated with mitochondria in addition to nuclear pores, and that reported phenotypes of many piRNA factor mutants include induction of PCD and/or germline mortality [ 75 , 140 144 ]. PCD is an important part of tissue differentiation, and piRNAs can prevent ectopic expression of somatic genes that might contribute to PCD or senescence of the germline [ 145 , 146 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which the regulation of PCD might still be relevant to eTudor and piRNA function, despite the loss of the DCD domain, remains to be elucidated, but there is evidence suggesting that it could be considerable. In the light of the putative evolutionary connection between the ancient form of PCD and the evolution of the eTudors and the piRNA network, it seems more explicable that conserved piRNA biogenesis factors Tudor-KH and MitoPLD/Zucchini are mitochondrially localized, perinuclear piRNA processing germ granules are also closely associated with mitochondria in addition to nuclear pores, and that reported phenotypes of many piRNA factor mutants include induction of PCD and/or germline mortality (Bronkhorst and Ketting 2018;Weick and Miska 2014;Houwing et al 2007;Tóth et al 2016;Aravin and Chan 2011;Manage et al 2020). PCD is an important part of tissue differentiation, and piRNAs can prevent ectopic expression of somatic genes that might contribute to PCD or senescence of the germline (Strome and Updike 2015;Meier, Finch, and Evan 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Associated with MIWI and MIWI2 via the binding of symmetrically dimethylated arginine (sDMA), TDRKH is the scaffold for interactions between PIWI-piRNA complexes and PNLDC1. The exonuclease trims the 3 -end of piRNA intermediates to their mature length (Ding et al, 2017;Zhang et al, 2017b;Bronkhorst and Ketting, 2018;Nishimura et al, 2018). The 3 -end of mature piRNA is 2 -O-methylated by HENMT1, yet correct 3 truncation is not necessary for 3 -end 2 -O-methylation (Yang et al, 2006;Zhai and Meyers, 2012;Peng et al, 2018).…”
Section: Primary Pirna Biogenesismentioning
confidence: 99%
“…Notably, LINE1 de-repression in spermatocytes does not necessarily lead to meiotic arrest, such as in Henmt1-knockout animals (Lim et al, 2015). Some mouse mutants of Miwi (Deng and Lin, 2002), Pnldc1 (Ding et al, 2017;Zhang et al, 2017c;Bronkhorst and Ketting, 2018;Nishimura et al, 2018), Tdrd5 (Yabuta et al, 2011;Ding et al, 2018), and Henmt1 (Lim et al, 2015), etc., still produce post-meiotic germ cells. Interestingly, although a large proportion of MIWI-piRNAs were thought to originate from non-transposon-related regions (Vourekas et al, 2012), LINE1 de-repression was found in Miwi-knockout mouse spermatids (Reuter et al, 2011).…”
Section: Repression Of Line1 Retrotransposons In Germ Cellsmentioning
confidence: 99%